2020
DOI: 10.1037/aap0000152
|View full text |Cite
|
Sign up to set email alerts
|

Foreigner objectification, cultural assets, and psychological adjustment in Asian American college students.

Abstract: Asian Americans have historically been subjected to foreigner objectification, a form of racial discrimination rooted in the "perpetual foreigner" stereotype. Foreigner objectification is related to multiple indicators of negative psychological adjustment and may be particularly salient for U.S.-born Asian Americans. This study examined whether cultural asset profiles (composed of ethnic-racial identity, American identity, and ethnic socialization) moderate the relationship between foreigner objectification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…The active integration group (46%) received frequent messages about maintaining heritage culture, few messages about avoiding outgroups or minimizing race, and the most messages about becoming American, treating everyone equally, and respecting diverse cultures. Four other studies evaluated profiles, combining ERS with other constructs: discrimination (Ajayi & Syed, 2014), ethnic‐racial identity (Wu et al., 2020; Xie et al., 2021), American identity (Wu et al., 2020), and model minority experiences (Kiang et al., 2019; Xie et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The active integration group (46%) received frequent messages about maintaining heritage culture, few messages about avoiding outgroups or minimizing race, and the most messages about becoming American, treating everyone equally, and respecting diverse cultures. Four other studies evaluated profiles, combining ERS with other constructs: discrimination (Ajayi & Syed, 2014), ethnic‐racial identity (Wu et al., 2020; Xie et al., 2021), American identity (Wu et al., 2020), and model minority experiences (Kiang et al., 2019; Xie et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Burrola (2013) found that cultural socialization exacerbated the relation of subtle discrimination to anxiety but only among U.S. born adolescents. Wu et al (2020) found that the positive relation of foreigner objectification to psychological distress was exacerbated by cultural assets profiles, especially those involving high or low levels of cultural socialization and less by the profile involving moderate socialization.…”
Section: Relation Of Ers To Child Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…In studies with a significant portion of Asian Americans in their samples, ERI commitment was found to be a stronger protective factor, but private regard for ERI was found to have a more exacerbating effect (Yip, 2017). In studies of Asian Americans specifically, ERI has been found to reduce the effects of experiencing racial discrimination on psychological distress, although it did not moderate the negative association between foreigner objectification and self-rated well-being (Wu et al, 2020). Our study intends to paint a clearer picture of the potential moderating effect of racial/ethnic identity importance within the understudied population of LGBT Asian Americans.…”
Section: Current Studymentioning
confidence: 99%
“…A growing body of research emphasizes the importance of examining the racist-gender stress model specifically for men of color attending university, especially predominantly White universities. In terms of college students of color broadly, research reveals how they experience many forms of racial discrimination in college contexts, such as assumptions of academic inferiority, receiving racist comments on assignments from professors, and being perceived as criminals or as foreigners by peers and university staff (Lee & Hopson, 2019; Wu et al, 2020). In addition to these forms of racial discrimination, men of color in particular report experiencing verbal assaults, emotions of hopelessness and despair, as well as feelings of being an outsider on campus, with this outsider status stemming from not seeing themselves as represented and cared for within the context of a university (Lott & Love, 2020).…”
Section: Racist-gender Stress Model and Men Of Colormentioning
confidence: 99%